Effect of smoking on differential white cell count and hemoglobin level in healthy smokers and controls: A comparative study - Sahar Mudassar, Mudassar Ali, Bilal Habib, Farukh Bashir, Shoaib Ahmed, Amna Mubeen, Amal Shaukat, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Cigarette smoking alters inflammation indicators, which has been linked to cardiovascular disease as well as inflammatory disorders. The toxicity of tobacco has an effect on the oxygen saturation of haemoglobin. Total and differential leukocyte count (DLC), as well as oxygen saturation of haemoglobin, were measured in healthy smokers and nonsmokers in order to determine whether or not they were smoking. Methods: The participants in this cross-sectional study totaled 80 persons in good health. A questionnaire was utilised to gather information on smoking habits as well as anthropometric measurements such as height, weight, and body mass index (BMI). In order to count total and DLC cells in blood samples, the MS-9 automated haematological cell counter was employed. The fingertip pulse oximeter was used to test the oxygen saturation of the haemoglobin. Results: Compared to non-smokers, smokers had higher TLC (P <0.001), lymphocyte (P< 0.002), granulocyte (P 0.01), and monocyte counts (P 0.03) and lower SpO2 (P 0.03). Conclusion: The study concluded that smokers' TLC, DLC, and haemoglobin oxygen saturation should be evaluated during diagnosis, interpretation, and therapy. The elevated TLC and DLCs seen in this study may be linked to chronic inflammation and increased CVD risk in smokers. Quitting smoking is therefore beneficial to health.